The Purpose, Design, and Promise of Medical Education Research Labs. (24th May 2022) - Gisondi, Michael A.; Michael, Sarah; Li-Sauerwine, Simiao; Brazil, Victoria; Caretta-Weyer, Holly A.; Issenberg, Barry; Giordano, Jonathan; Lineberry, Matthew; Olson, Adriana Segura; Burkhardt, John C.; Chan, Teresa M.
Abstract : Medical education researchers are often subject to challenges that include lack of funding, collaborators, study subjects, and departmental support. The construct of a research lab provides a framework that can be employed to overcome these challenges and effectively support the work of medical education researchers; however, labs are relatively uncommon in the medical education field. Using case examples, the authors describe the organization and mission of medical education research labs contrasted with those of larger research team configurations, such as research centers, collaboratives, and networks. They discuss several key elements of education research labs: the importance of lab identity, the signaling effect of a lab designation, required infrastructure, and the training mission of a lab. The need for medical education researchers to be visionary and strategic when designing their labs is emphasized, start-up considerations and the likelihood of support for medical education labs is considered, and the degree to which department leaders should support such labs is questioned.